Loan payment prediction using rough sets - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
In small business loans, there is always a risk for nonpayment or non-refunding of loans though very detailed examinations are made about the company. In this study, behaviors that increase the risk in loans or causing non-refunding are tried to be determined by using the rough set approach. This paper will demonstrate that rough sets model is applicable to a wide range of practical problems pertaining to loan payment prediction. Moreover, the results show that the rough sets model is a promising alternative to the conventional methods for financial prediction.
Keywords: loan payment failure; prediction; rough sets; classification; INSOLVENCY